1992
DOI: 10.21273/horttech.2.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biological and Chemical Control of Greenhouse Whitefly on Poinsettia Stock Plants

Abstract: A demonstration study was conducted to compare the effectiveness of biological and chemical control treatments on the greenhouse whitefly (GHWF) (Trialeurodes vaporariorum, Westwood) using poinsettia (Euphorbia pulcherrima Wild.) stock plants. Two identical greenhouse compartments, each containing 84 stock plants, were used. In the biological control compartment, three biweekly releases of Encarsia formosa (EF) were made, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Inundative releases of E. formosa have been successful in some instances for control of T. vaporariorum on poinsettia (76). Control of B. argentifolii with weekly releases of more than three adult parasitoids per plant per week, has not been accomplished (56, 90).…”
Section: Efficacy Of Release Rates and Methodsmentioning
confidence: 99%
“…Inundative releases of E. formosa have been successful in some instances for control of T. vaporariorum on poinsettia (76). Control of B. argentifolii with weekly releases of more than three adult parasitoids per plant per week, has not been accomplished (56, 90).…”
Section: Efficacy Of Release Rates and Methodsmentioning
confidence: 99%
“…The total release rate of 9.2 EF per plant is considerably lower than that implemented by other researchers for both GHWF and SPWF control studies (Parrella et al, 1991: Benuzzi et al, 1990McMahon et al, 1992). At a cost of $10.00 per 1000 EF and Fig.…”
mentioning
confidence: 68%
“…Poinsettias are an excellent crop for biological control, as the crop typically is grown as a monoculture and there are only two insect pests of significance: the GHWF and the sweetpotato whitefly (SPWF) (Ecke et al, 1990). McMahon et al (1992) showed that poinsettia stock plants could produce terminal stem cuttings free of GHWF adults through three biweekly releases of 9.5 EF per plant. Releases were made when the GHWF infestation was small (i.e., two GHWF per plant), which is essential when implementing biological control agents (Albert, 1990).…”
mentioning
confidence: 99%